3D Micro‐Printing: A new Era for Med‐Tech Applications: How three‐dimensional thinking is turning a piece of material into smart medical devices. Issue 1 (5th January 2018) - Steimle, Alexander
Abstract: In recent years, 3D printing has attracted increasing attention in many industries. From bioprinting of living organs to engine and airplane components, a variety of 3D printing techniques are already in use today, mainly differentiated by the additive or sub‐tractive manufacturing approach. But what's the application potentiality in the med‐tech industry with regards to 3D printing at micro‐scale? And how innovative three‐dimensional thinking can tackle human diseases such as the retinal vein occlusion (RVO) and create transformative products?